Semiconductor devices in solid-state/hybrid circuit breakers: current status and future trends - Gu, Chunyang; Wheeler, Pat; Castellazzi, Alberto; Watson, Alan J.; Effah, Francis (MDPI, 2017)
Circuit breakers (CBs) are the main protection devices for both alternating current (AC) and direct current (DC) power systems, ranging from tens of watts up to megawatts. This paper reviews the current status for solid-state circuit breakers (SSCBs) as well as hybrid circuit breakers (HCBs) with semiconductor power devices. A few novel SSCB and HCB concepts are described in this paper, including advantage and limitation discussions of wide-band-gap (WBG) devices in basic SSCB/HCB configuration by simulation and 360 V/150 A experimental verifications. Novel SSCB/HCB configurations combining ultra-fast switching and high efficiency at normal operation are proposed. Different types of power devices are installed in these circuit breakers to achieve adequate performance. Challenges and future trends of semiconductor power devices in SSCB/HCB with different voltage/power levels and special performance requirements are clarified.